Building Capacity for Cyberbiosecurity Training - Richardson, Lauren C.; Lewis, Stephen M.; Burnette, Ryan N. (Frontiers in Bioengineering and Biotechnology, 2019)
Cyberbiosecurity lies at the intersection of cybersecurity and biosecurity and addresses the protection of valuable biological material and associated information. As an emerging concept, cyberbiosecurity requires the integration of training strategies targeted to both current and future professionals; as well as an increased awareness in the wider stakeholder community. As the discrete discipline of cyberbiosecurity continues to develop, initial training efforts are likely to include workshops and specialized training that bridge the disciplines of information technology (IT) and life sciences. Potential threats, risks, and vulnerabilities will be defined, cooperative relationships formed, and collaborative solutions developed. As the scope of the training framework for assessing potential threats is adapted to various audiences, in-service trainings will ensure awareness and understanding of threats relevant to specific industries. This framework may also be incorporated into existing curricula across IT and science fields. The scope of potential threats is vast, and eventual specialization will likely fall within the realm of IT professionals, who carry the capability for action. In this paper, we identify stakeholders in the development of cyberbiosecurity training; discuss current training methods, educational requirements, and credentialing for professionals in cybersecurity, biosecurity, and life sciences; suggest mechanisms for integration of cyberbiosecurity training into existing training approaches; and discuss potential for future development of specialized professionals.